ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PADA E-COMMERCE SHOPEE - Fani Rahmasari; Anna Probowati; Dewi Shanti Nugrahani (STIE Rajawali Purworejo, 2025)
This study aims to analyze the factors that influence consumer purchasing decisions on the Shopee e-commerce platform. The variables studied include promotion (X1), price (X2), product completeness (X3), and product quality (X4) on purchasing decisions (Y). This study uses a quantitative approach with a survey method, where data is collected through questionnaires distributed to active Shopee users. The research sample consisted of 100 respondents selected using a specific sampling technique (eg purposive sampling). Data analysis was carried out using multiple linear regression techniques to determine the effect of each independent variable on the dependent variable. The results of the study show that all independent variables, namely promotion, price, product completeness, and product quality, simultaneously have a significant effect on consumer purchasing decisions. Partially, the variables promotion (X1), price (X2), product completeness (X3), and product quality (X4) on purchasing decisions (Y) have the greatest influence on purchasing decisions. These findings emphasize the importance of a marketing strategy that focuses on attractive promotions, competitive pricing, completeness of products offered, and improving product quality to improve consumer purchasing decisions on Shopee e-commerce. This research is expected to contribute to the development of marketing strategies in e-commerce, especially for Shopee, as well as being a reference for further research in similar fields.Keywords: purchasing decisions, promotions, prices, product completeness, product quality, Shopee e-commerce